The Effect of Stair up and down Training on Jump Height and Smash Point Obtainment in Male Volleyball Athletes - Milla Hamma Azzahroh; Fajar Syamsudin (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Smash is one of the determinants of victory in the game of volleyball. To master a good smash technique, strong leg muscles are needed. The purpose of this study is to determine the effect of training up and down stairs on the height of smash jump and the acquisition of smash points in male volleyball athletes of SMA Negeri 1 Bandar. The research design uses the design of one pretest-postest group. The method used is a quantitative method. The sample of this study is all male volleyball athletes of SMA Negeri 1 Bandar as many as 10 athletes determined by total sampling. The technical instruments for data collection are measurements and tests in the form of vertical jump tests and smash tests. The data analysis technique uses the t. The results of this study show that 1) There is an effect on the practice of going up and down stairs on the jump height of male volleyball athletes at SMA Negeri 1 Bandar, 2) There is an effect of training up and down stairs on the acquisition of smash points in male volleyball athletes of SMA Negeri 1 Bandar. With t test results vertical jump value sig. (2-tailed)=0.000 and t-calculate=27,650 and the results of the t test are smash results, the value of sig. (2-tailed) =0.000 and t count = 10.984. The conclusion of this study shows that there is a significant increase in the height of smash jump and the acquisition of smash points in male volleyball athletes of SMA Negeri 1 Bandar. Advice for trainers can provide training to improve jump height. For athletes, they can train their leg muscles to increase jump height. For future research, it can be used as a scientific study in future research.